Penerapan Hukum Dan Praktiknya Atas Tanggung Jawab Negara, Masyarakat Dan Keluarga Dalam Perlindungan Anak - Siregar, Rospita A; Lengkong, Lonna Yohanes; Panjaitan, Petrus Irwan (Jurnal Hukum Mimbar Justitia, 2024)
AbstrakAnak bagian anggota keluarga, kerapkali menjadi sasaran kekerasan baik itu fisik, seksual atau dimanfaatkan untuk diperkerjakan. Menjadi peminta-minta, pemulung, pekerja bangunan bahkan pekerja seksual, atau diperdagangkan, dimedia cetak/elektronik memberitakan menimbulkan reaksi dan simpati, tetapi larangan agar anak itu terlindungi tidak tersampaikan.  Jawaban atas masalah hukum yang dikaji digunakan metode Tinjauan juridis normatif mengkaji bentuk tanggungjawab negara, masyarakat, dan keluarga dalam Perlindungan Anak di Indonesia. Hasil penelitian menegaskan Upaya perlindungan anak dilaksanakan oleh negara melalui terbitnya UU No. 23 Tahun 2002 Jo. UU No. 35 Tahun 2014 tentang Perlindungan Anak, UU Sistem Peradilan Pidana Anak. Hak  anak diakui, dalam UU No 27 Tahun 2007 tentang Pemberantasan Tindak Pidana Orang, Undang-undang RI No. 1 Tahun 2000 tentang pengesahan ILO convention No. 182 concening the pro hibition and imidiate action for the elemation of the worse form of child labor (konfensi ILO No 182, masih perlu tanggungjawab negara, tanggung keluarga serta masyarakat. AbstractChildren, as part of the family, often become targets of violence, whether physical, sexual, or being exploited for labor. Becoming beggars, scavengers, construction workers, or even sex workers, or being trafficked, is reported in print/electronic media, evoking reactions and sympathy, but the prohibition to protect the child is not conveyed.  The answer to the legal issue under review uses the normative juridical review method to examine the forms of responsibility of the state, society, and family in Child Protection in Indonesia. The research results emphasize that child protection efforts are carried out by the state through the issuance of Law No. 23 of 2002 Jo. Law No. 35 of 2014 concerning Child Protection, the Child Criminal Justice System Law. Children's rights are recognized in Law No. 27 of 2007 concerning the Eradication of Human Trafficking, and the Republic of Indonesia Law No. 1 of 2000 concerning the ratification of ILO Convention No. 182 concerning the Prohibition and Immediate Action for the Elimination of the Worst Forms of Child Labor (ILO Convention No. 182). However, there is still a need for state, family, and community responsibility.